Equilibrium-point control of human elbow-joint movement under isometric environment by using multichannel functional electrical stimulation - Matsui, Kazuhiro; Hishii, Yasuo; Maegaki, Kazuya; Yamashita, Yuto; Uemura, Mitsunori; Hirai, Hiroaki; Miyazaki, Fumio (Frontiers in Neuroscience, 2014)
Functional electrical stimulation (FES) is considered an effective technique for aiding quadriplegic persons. However, the human musculoskeletal system has highly nonlinearity and redundancy. It is thus difficult to stably and accurately control limbs using FES. In this paper, we propose a simple FES method that is consistent with the motion-control mechanism observed in humans. We focus on joint motion by a pair of agonist-antagonist muscles of the musculoskeletal system, and define the"electrical agonist-antagonist muscle ratio (EAA ratio)" and "electrical agonist-antagonist muscle activity (EAA activity)" in light of the agonist-antagonist muscle ratio and agonist-antagonist muscle activity, respectively, to extract the equilibrium point and joint stiffness from electromyography (EMG) signals. These notions, the agonist-antagonist muscle ratio and agonist-antagonist muscle activity, are based on the hypothesis that the equilibrium point and stiffness of the agonist-antagonist motion system are controlled by the central nervous system. We derived the transfer function between the input EAA ratio and force output of the end-point. We performed some experiments in an isometric environment using six subjects. This transfer-function model is expressed as a cascade-coupled dead time element and a second-order system. High-speed, high-precision, smooth control of the hand force were achieved through the agonist-antagonist muscle stimulation pattern determined by this transfer function model.